Sedentary lifestyle in active children admitted to a summer sportschool - Fainardi, V.; Scarabello, C.; Iovane, B.; Errico, et al., M. K. (Acta Biomedica Atenei Parmensis, 2009)
Aim of this study was to investigate the sedentary patterns of school-aged active children admitted to a summer sport school. One hundred-twelve children aged 9-11 years were interviewed through a questionnaire about sedentary behaviours and nutrition habits. Seventy-one per cent of children reported they watch TV seven days a week, girls less than boys (84±45 minutes vs 110±75 minutes) (t=2,056; p=0,042). The habit of TV viewing during meals was widespread (38% breakfast, 31% lunch, 62% dinner, 18% every meal). The prevalence of overweight or obesity (58.5%) was significantly higher among boys watching TV at dinner compared to the boys viewing TV only in the afternoon (35%) (χ2=4.976; p=0.026). Fifty-seven per cent of children (65% boys) were accustomed to nibble snacks during TV viewing, and this habit was widespread in overweight or obese boys (χ2=4.546; p=0.033). The dietary patterns of children watching TV include more snack foods and fewer fruits than the dietary patterns of the same children exercising (χ2=4.199 p=0.040). Also in active children the habit to watch television is widespread and, in spite of the tendency to physical activity, 46% of them were overweight or obese; in fact the time spent looking at a TV may be associated to overweight/obesity and this relationship could be explained by the amount of high-density foods  consumption during inactivity. Playing video games, read a book and listening to music are sedentary lifestyle patterns but these seem not to represent a risk factor for an increased BMI.